1999
DOI: 10.1142/s0217979299003180
|View full text |Cite
|
Sign up to set email alerts
|

Upper Critical Field of Unconventional Superconductors From Chemical Equilibrium

Abstract: We have shown previously that many normal state properties of high Tc superconductors in zero magnetic field can be understood in terms of a single universal function f(t) in the scaled variable t=T/T*, where T* is connected with temperature independent gap 2Δ=2kBT*, which gives the binding energy of a pair in analogy with dissociation of molecules. The function f(t) determines the fraction of bosons (B++) and fermions (h+) at temperature T and it is obtained from the mathematical treatment of chemical equilib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It was shown that the phenomenology describes reasonably well the data in the underdoped Y-Ba-Cu-O family but fails to describe these compounds in the optimally doped regime or underdoped La-Sr-Cu-O. The influence of the existence of the fermion bound states above T c was also considered in [138] and the theory of chemical equilibrium between these bound states and single fermions was applied in [139] to explain the normal state properties of HTSC (see also [140] which considers the BEC of such pairs).…”
Section: Bcs-bose Crossover and Pseudogap: Survey Of The Current Lite...mentioning
confidence: 99%
“…It was shown that the phenomenology describes reasonably well the data in the underdoped Y-Ba-Cu-O family but fails to describe these compounds in the optimally doped regime or underdoped La-Sr-Cu-O. The influence of the existence of the fermion bound states above T c was also considered in [138] and the theory of chemical equilibrium between these bound states and single fermions was applied in [139] to explain the normal state properties of HTSC (see also [140] which considers the BEC of such pairs).…”
Section: Bcs-bose Crossover and Pseudogap: Survey Of The Current Lite...mentioning
confidence: 99%